2019
DOI: 10.3389/fpls.2019.00284
|View full text |Cite
|
Sign up to set email alerts
|

PhDHS Is Involved in Chloroplast Development in Petunia

Abstract: Deoxyhypusine synthase (DHS) is encoded by a nuclear gene and is the key enzyme involved in the post-translational activation of the eukaryotic translation initiation factor eIF5A. DHS plays important roles in plant growth and development. To gain a better understanding of DHS, the petunia (Petunia hybrida) PhDHS gene was isolated, and the role of PhDHS in plant growth was analyzed. PhDHS protein was localized to the nucleus and cytoplasm. Virus-mediated PhDHS silencing caused a sectored chlorotic leaf phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 78 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…Western blot analyses were performed according to the methods of Liu et al (2019) . The peptides ( Supplementary Table S4 ) expressed in Escherichia coli of three proteins, PamCS (Peaxi162Scf00402g00612.1), PaPDC2 (pyruvate decarboxylase-2, Peaxi162Scf00014g00030.1) and PaGELP (GDSL, esterase/lipase, Peaxi162Scf00038g01135.1), and the synthetic acetylation peptides (QQFNKacKMNS) of the protein PaGELP255Kac, were used as antigens for antibody production in rabbits from Diaan ( http://www.dia-an.cn/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analyses were performed according to the methods of Liu et al (2019) . The peptides ( Supplementary Table S4 ) expressed in Escherichia coli of three proteins, PamCS (Peaxi162Scf00402g00612.1), PaPDC2 (pyruvate decarboxylase-2, Peaxi162Scf00014g00030.1) and PaGELP (GDSL, esterase/lipase, Peaxi162Scf00038g01135.1), and the synthetic acetylation peptides (QQFNKacKMNS) of the protein PaGELP255Kac, were used as antigens for antibody production in rabbits from Diaan ( http://www.dia-an.cn/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence shows that the expression of DHS could spatially and temporally change via the developmental stages. In Petunia, suppression of DHS caused abnormal chloroplast development in the leaves and delayed leaf senescence [ 32 ]. However, in Arabidopsis, the leaf-specific suppression of DHS resulted in growth enhancement without any negative pleiotropic effects [ 33 ] despite an earlier study that demonstrated the pleiotropic effects of suppressed DHS expression in the same plants [ 4 ].…”
Section: Two Steps Of Hypusinationmentioning
confidence: 99%
“…Suppressed DHS caused increased root biomass, bigger leaves, and enhanced seed yield in Arabidopsis during drought stress [ 4 ]. Sectored chlorotic leaves were also detected in Petunia plants, suggesting that PhDHS is involved in their chloroplast development [ 32 ], indicating a functional difference between different plant species. DHS silencing caused extended leaf longevity and increased thickness of the leaves, with reducing sugar and starch contents indicating the compensation of energy loss.…”
Section: Two Steps Of Hypusinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorophyll content was determined according to our previously described protocol (Liu et al 2019). Approximately 1.5 g of leaves were harvested and freeze-dried, and three replicate methanol extractions were prepared.…”
Section: Determination Of Chlorophyll Contentmentioning
confidence: 99%